Pluralisme Agama Perspektif Raimundo Panikkar: Kontribusinya untuk Keberagaman Agama di Kota Kupang - Taman, Heribertus Kurnia; Lelono, Martinus Joko (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
The plurality of religions and cultures in Kupang City often creates challenges, such as the potential for conflict or misunderstanding between religious and cultural groups. This situation sometimes disrupts the tolerance of religious life in Kupang. In addition, this situation often leads to conflicts between small groups (Muslims) and large groups (Christians). In this context, the pluralist views of Raimundo Panikkar, a prominent theologian and philosopher of religion, provide a unique perspective on understanding religious diversity. Through an analysis of Panikkar’s key concepts, such as “Culture of Religious Encounter,” “Religious Dialogue,” and “Transcendental Unity,” this paper attempts to outline how Panikkar’s thinking can serve as a foundation for understanding interfaith dialogue in Kupang City. The study also presents findings using a literature review method to gain new insights into Panikkar’s contribution to religious diversity in the region. Through this study, it is hoped that an understanding of Panikkar’s view of religious pluralism can serve as a foundation for developing harmony within the rich and precious religious diversity.  Abstrak Pluralitas agama dan budaya di Kota Kupang, tidak jarang memunculkan tantangan, seperti potensi konflik atau ketidakpahaman antar kelompok agama dan budaya. Situasi ini terkadang mengganggu toleransi hidup beragama di kota Kupang. Di samping itu juga, situasi ini seringkali memunculkan konflik antara kelompok yang berjumlah sedikit (Muslim) dan kelompok yang berjumlah banyak (Kristen). Dalam konteks ini, pandangan Pluralisme Raimundo Panikkar, seorang teolog dan filsuf agama terkemuka, memberikan perspektif unik dalam memahami keberagaman agama. Melalui analisis konsep-konsep kunci Panikkar, seperti “Budaya Perjumpaan Religius,” “Dialog Agama,” dan “Kesatuan Transendental,” tulisan ini mencoba menguraikan bagaimana pemikiran Panikkar dapat menjadi landasan untuk memahami dialog antaragama di Kota Kupang. Studi ini juga menyajikan temuan dengan menggunakan metode kajian pustaka untuk mendapatkan pandangan yang baru tentang kontribusi Panikkar terhadap keberagaman agama di daerah ini. Melalui kajian ini, diharapkan pemahaman tentang pandangan pluralisme agama Panikkar dapat menjadi landasan untuk mengembangkan kerukunan dalam keragaman agama yang begitu kaya dan berharga